Performative revolution in Egypt an essay in cultural power - Alexander, Jeffrey C. 1947-4eauthor (Bloomsbury Academic, 2011)
The author examines what was new about Egypt's revolution in spring 2011 - why it was so compelling to watch, what made it so effective and does it have implications for democratic movements internationally?